Integrated bioprocess for structured lipids, emulsifiers and biodiesel production using crude acidic olive pomace oils. (February 2022) - Heinzl, Giuditta C.; Mota, Danyelle A.; Martinis, Valentina; Martins, Ana Sofia; Soares, Cleide M.F.; Osório, Natália; Gominho, Jorge; Madhavan Nampoothiri, K.; Sukumaran, Rajeev K.; Pereira, Helena; Ferreira-Dias, Suzana
Graphical abstract: Highlights: Valorization of olive pomace oil (OPO), a by-product of olive oil industry. Acidic crude OPO used for structured lipids, emulsifiers and biodiesel production. Regioselective lipases used as biocatalysts in solvent-free media. High activity and operational stability of immobilized Rhizomucor miehei lipase. Abstract: Olive pomace oil (OPO), a by-product of olive oil industry, is directly consumed after refining. The novelty of this study consists of the direct use of crude high acidic OPO (3.4–20% acidity) to produce added-value compounds, using sn -1, 3-regioselective lipases: (i) low-calorie dietetic structured lipids (SL) containing caprylic (C8:0) or capric (C10:0) acids by acidolysis or interesterification with their ethyl esters, (ii) fatty acid methyl esters (FAME) for biodiesel, and (iii) sn -2 monoacylglycerols (emulsifiers), as by-product of FAME production by methanolysis. Immobilized Rhizomucor miehei lipase showed similar activity in acidolysis and interesterification for SL production (yields: 47.8–53.4%, 7 h, 50℃) and was not affected by OPO acidity. Batch operational stability decreased with OPO acidity, but it was at least three-fold in interesterification that in acidolysis. Complete conversion of OPO into FAME and sn -2 monoacylglycerols was observed after 3 h-transesterification (glycerol stepwise addition) and lipase deactivation was negligeable after 11 cycles.